A Case of Hydrocele Stone with Its Composition Analysis - Masayoshi Zaitsu; Koji Mikami; Yuta Takeshima; Takumi Takeuchi (Case Reports in Medicine)
Hydrocele stones are freely mobile calcified bodies lying between the tunica vaginalis layers, and they are relatively rare. We present here another case of hydrocele stone incidentally discovered when castration was being undergone for the endocrine treatment of prostate cancer. A 71-year-old man was diagnosed as stage D2 prostate cancer with his prostate-specific antigen 387 ng/ml. A white smooth stone of 11 mm in diameter was incidentally found moving freely in the right hydrocele space during castration. The hydrocele stone was of yellow hard center with white materials around it. Crystallographical analysis of the hydrocele stone by a infrared spectrophotometer showed that the center was composed of 64% calcium carbonate and 36% calcium phosphate, while the outer portion was protein. Our case is the fourth where crystallographical analysis was reported for hydrocele stones.